Extracorporeal circulation (ECLS/ECMO) for cardio-circulatory failure: summary of the S3 guideline - Boeken, Udo; Assmann, Alexander; Beckmann, Andreas; Schmid, Christof; Werdan, Karl; Michels, Guido; Miera, Oliver; Schmidt, Florian; Klotz, Stefan; Starck, Christoph; Pilarczyk, Kevin; Rastan, Ardawan; et al. (The thoracic and cardiovascular surgeon, 2021)
Thieme E-Books & E-Journals
Artikel online veröffentlicht: 21. September 2021
Gesehen am 15.12.2022